(untitled) (Globalization and Business, 2018)
The usage of natural resources is to consume the natural resources to satisfy the needs of the society. At the same time, the traditional economic model of the revenue and welfare of the goodness suggests the interaction of household, firms and market access.A. All revenues are spent (not stored);B. There is no international trade;C. This model is a locked self-contained system. The economy can be divided into two subsystems - pro-duction and consumption. Each of them directly or indirectly uses environmental resources and creates "waste products" that contain all types of material substance (substance-Lat-in-origin, which is the basis for the first basis of all things and events) which can be exhibited in the atmosphere, discharged into water bodies or be deployed on the soil or in the ground. An important component of "waste products" is also en-ergy wastes in the form of heat, noise, magnetic field, radia-tion, vibration, etc. A substantial amount of material waste can be returned to production, and the rest is partial. Energy wastes can also be used as partially If the economic activity is within the borders, the environment has the ability to absorb, pollute and waste to assimilate the environmental system without damaging it then the ecological-economic damage will not arise. In the case of economic activity the balance of ecosystems is broken and the ecological economic consequences of negative ecological-economic results are created. Thus, externals (externals, which are not taken into account by their implementers and therefore do not affect its decisions) regulation of natural usage of processes seeks to interfere with the state's interference in the market economy by means of administrative or economic leverage. This can be explained by the market inefficiency, due to the impossibility of self-regulation of ecologic-economic systems at the expense of natural market mechanisms, as well as the peculiarities of a number of countries that are due to certain stages of their development.